KARAKTERISTIK PROSES GASIFIKASI TEMPURUNG KELAPA MENGGUNAKAN UPDRAFT GASIFIER TIPE HISAP - Icha Syahrotul Anam; Bambang Purwantana; Radi Radi (Jurnal Teknologi Terapan, 2022)
Energy demand continues to increase in line with the increasing population which results in high energy consumption. Utilization of biomass waste such as coconut shells as an alternative energy source is very beneficial, because it can reduce dependence on fuel oil. One of the technologies that can be used to produce alternative energy is biomass gasification. The purpose of this study was to determine the character of the biomass gasification process using a suction type updraft gasifier with varying the size of the material and air flow rate. The biomass used was coconut shell with a moisture content of 8-10%. The research method used by varying the size of the material and the air flow rate. The weight of the material tested was 5 kg with additional 200 grams of charcoal. The results showed that coconut shell gasification using updraft gasifier with suction type was able to produce combustible gas with the characteristics of the gasification process including the effective gasification time of 15-21 minutes, gasification process temperature > 700° C, flame temperature 400-800° C, mass of charcoal and ash 138-223 grams, tar mass 38-95gram and effectiveness 25-94%. The flames characteristic at an air flow rate of 0.17m/s tend to be solid, at an air flow rate of 0.23 m/s the flames are high, and 0.3 m/s the flames are mostly filled with smoke. The highest effectiveness is achieved at a variation of 0.17 m/s, which indicates that with the increasing rate of incoming air, the effectiveness of gasification will be lower.